Ethical Solutions to the Problem of Organ Shortage - Sterri, Aksel Braanen (Cambridge quarterly of healthcare ethics, 2022)
Organ shortage is a major survival issue for millions of people worldwide. Globally 1.2 million people die each year from kidney failure. In this paper, we critically examine and find lacking extant proposals for increasing organ supply, such as opting in and opt out for deceased donor organs, and parochial altruism and paired kidney exchange for live organs. We defend two ethical solutions to the problem of organ shortage. One is to make deceased donor organs automatically available for transplant without requiring consent from the donor or their relatives. The other is for society to buy nonvital organs in a strictly regulated market and provide them to people in need for free.